2018
DOI: 10.29271/jcpsp.2018.07.514
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Of Endoscopic Management Of Post Living Donor Liver Transplant Anastomotic Strictures

Abstract: Endoscopic management of post-LDLT AS has an efficacious long-term outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Meanwhile, based on theoretical analysis, compared with single EPBD, this technique will bluntly dilate the nipples along the direction of common bile duct (11-o’clock position), reduce the edema caused by the compression of the pancreatic duct opening, and decline the incidence of pancreatitis. Published studies showed that there was no significant difference in the stone removal rates between EST and ESBD 10–21. This study revealed the same total stone clearance rates for EST, ESBD, and ISBD.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…Meanwhile, based on theoretical analysis, compared with single EPBD, this technique will bluntly dilate the nipples along the direction of common bile duct (11-o’clock position), reduce the edema caused by the compression of the pancreatic duct opening, and decline the incidence of pancreatitis. Published studies showed that there was no significant difference in the stone removal rates between EST and ESBD 10–21. This study revealed the same total stone clearance rates for EST, ESBD, and ISBD.…”
Section: Discussionsupporting
confidence: 67%
“…Published studies showed that there was no significant difference in the stone removal rates between EST and ESBD. [10][11][12][13][14][15][16][17][18][19][20][21] This study revealed the same total stone clearance rates for EST, ESBD, and ISBD. However, there is a higher first stone clearance rate of ISBD than EST and ESBD, indicating the potential of ISBD in reducing hospital stay, costs, and repeat complications.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Sir, Endoscopic retrograde cholangiopancreatography (ERCP) is one of the important diagnostic and treatment methods for hepatobiliary and pancreatic diseases. 1 Therapeutic ERCP has many complications for its many operations, long operating time, and many applications. Pancreatitis and hyperamylasemia are common complications after ERCP.…”
mentioning
confidence: 99%